2015
DOI: 10.1021/jacs.5b01155
|View full text |Cite
|
Sign up to set email alerts
|

Design and Mechanism of Tetrahydrothiophene-Based γ-Aminobutyric Acid Aminotransferase Inactivators

Abstract: Low levels of γ-aminobutyric acid (GABA), one of two major neurotransmitters that regulate brain neuronal activity, are associated with many neurological disorders, such as epilepsy, Parkinson’s disease, Alzheimer’s disease, Huntington’s disease, and cocaine addiction. One of the main methods to raise the GABA level in human brain is to use small molecules that cross the blood-brain barrier and inhibit the activity of γ-aminobutyric acid aminotransferase (GABA-AT), the enzyme that degrades GABA. We have design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…As GABA-AT is a key enzyme involved in the GABA metabolic pathways and GABA shunt, the inhibitors of this enzyme can increase the level of GABA, and have a potency to cure some diseases derived from the decrease of GABA. After vigabatrin was used as an irreversible GABA-AT inhibitor to cure epilepsy in clinic [18] , many other GABA analogs were synthesized for the inhibitory evaluation of GABA-AT [16,[19][20][21][22][23][24][25][26][27] . Moreover, gabaculine, a naturally occurring neurotoxin produced by the bacteria Streptomyces toyocaensis No.…”
Section: Discussionmentioning
confidence: 99%
“…As GABA-AT is a key enzyme involved in the GABA metabolic pathways and GABA shunt, the inhibitors of this enzyme can increase the level of GABA, and have a potency to cure some diseases derived from the decrease of GABA. After vigabatrin was used as an irreversible GABA-AT inhibitor to cure epilepsy in clinic [18] , many other GABA analogs were synthesized for the inhibitory evaluation of GABA-AT [16,[19][20][21][22][23][24][25][26][27] . Moreover, gabaculine, a naturally occurring neurotoxin produced by the bacteria Streptomyces toyocaensis No.…”
Section: Discussionmentioning
confidence: 99%
“…(2S,4S)-4-Aminotetrahydrothiophene-2-carboxylic acid hydrochloride (130) was designed to inactivate GABA-AT by either an elimination-Michael addition mechanism (pathway a) or elimination-enamine mechanism (pathway b, Scheme 29) from 131; it does something completely different. 151 The X-ray crystal structure of GABA-AT inactivated by (2S,4S)-130 at 1.66 Å (Figure 10) revealed a nonplanar five-membered ring covalently bound to the PLP; Lys329 was not modified, indicating that neither of the hypothesized inactivation pathways was occurring. Also, a heretofore unreported intermolecular nonbonded S•••••O interaction between the sulfur atom of 130 and the carboxylate oxygen of Glu270 was observed.…”
Section: Michael Addition and Enamine Mechanisms Via Eliminationmentioning
confidence: 99%
“…Given the aromatization mechanisms for gabaculine (136), 4amino-4,5-dihydrothiophene-2-carboxylic acid (144), and Lcycloserine (146), it would seem redundant to investigate the mechanism of inactivation of GABA-AT by (S)-4-amino-4,5dihydrofuran-2-carboxylic acid (151), which was synthesized and reported to be an inactivator of GABA-AT. 176 However, a detailed investigation into its inactivation mechanism revealed that this heterocycle does not proceed by an aromatization mechanism.…”
Section: Aromatization Mechanismsmentioning
confidence: 99%
“…Silverman and co-workers have designed, synthesized and evaluated a variety of GABA-AT inhibitors. These inhibitors include heteroaromatic substrates [ 38 , 39 ], fluorinated and conformationally restricted fluorinated analogues [ 40 , 41 , 42 ], bioisosters of carboxylic acids [ 43 ], and some tetrahydrothiophene analogues and their inactivation mechanism [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%